Iron deprivation enhances transcriptional responses to in vitro growth arrest of Mycobacterium tuberculosis - Alebouyeh, Sogol; Cárdenas-Pestana, Jorge A.; Vazquez, Lucia; Prados-Rosales, Rafael; Del Portillo, Patricia; Sanz, Joaquín; Menéndez, Maria Carmen; García, Maria J. (Frontiers in Microbiology, 2022)
The establishment of Mycobacterium tuberculosis (Mtb) long-term infection in vivo depends on several factors, one of which is bacterial availability of key nutrients such as iron. The relation between Fe deprivation inside and outside the granuloma, and the capacity of Mtb to accumulate lipids and persist in the absence of growth is not well understood. In this context, current knowledge of how Mtb modifies its lipid composition in response to growth arrest, depending on iron availability, is scarce. To shed light on these matters, in this work we compare genome-wide transcriptomic and lipidomic profiles of Mtb at exponential and stationary growth phases using cultures with glycerol as a carbon source, in the presence or absence of iron. As a result, we found that transcriptomic responses to growth arrest are iron dependent for as many as 714 genes (iron-growth interaction contrast, FDR<0.05), and that, in a majority of these genes, iron deprivation enhances the magnitude of the transcriptional responses to growth arrest in either direction. On the one hand, genes whose upregulation upon growth arrest is enhanced by iron deprivation were enriched in functional terms related to homeostasis of ion metals, and responses to several stressful cues considered cardinal features of the intracellular environment. On the other hand, genes showing negative responses to growth arrest that are stronger in iron-poor medium were enriched in energy production processes (TCA cycle, NADH dehydrogenation and cellular respiration), and key controllers of ribosomal activity shut-down, such as the T/A system mazE6/F6. In spite of these findings, a main component of the cell envelope, lipid PDIM, was not detected in the stationary phase regardless of iron availability, which suggests that changes in the lipid repertoires during Mtb adaptation to non-dividing phenotypes appear to be iron-independent. Taken together, our results indicate that environmental iron levels act as a key modulator of the intensity of the transcriptional adaptations that take place in the bacterium upon its transition between dividing and dormant-like phenotypes in vitro.